2021
DOI: 10.3892/etm.2021.10198
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection over bile reflux: No influence on the severity of endoscopic or premalignant gastric lesion development

Abstract: Helicobacter (H.) pylori infection and duodenogastric reflux (DGR) are both linked to endoscopic and premalignant gastric lesion development, but it is still unclear whether they are independent or have a causal relationship. This study investigated the histologic gastric changes in patients with primary DGR and H. pylori infection, as well as their endoscopic findings, symptoms, drug consumption, and social behavior in comparison with patients presenting only DGR. The study included 560 patients with primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
1
6
0
7
Order By: Relevance
“…32.2%), but the association was not statistically significant. 51 Mechanistically, chronic Hp infection contributes to antroduodenal motility disorder, which indirectly induces the retrograde passage of alkaline duodenal content into the stomach. 51 Additionally, the presence of DGR does not interfere with the presence and severity of H. pylori .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32.2%), but the association was not statistically significant. 51 Mechanistically, chronic Hp infection contributes to antroduodenal motility disorder, which indirectly induces the retrograde passage of alkaline duodenal content into the stomach. 51 Additionally, the presence of DGR does not interfere with the presence and severity of H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“… 51 Mechanistically, chronic Hp infection contributes to antroduodenal motility disorder, which indirectly induces the retrograde passage of alkaline duodenal content into the stomach. 51 Additionally, the presence of DGR does not interfere with the presence and severity of H. pylori . 52 Therefore, together with our findings presented herein, the eradication of Hp without the treatment of DGR might not be sufficient to prevent gastric epithelial carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Szőke et al demonstrated that smoking is associated with H. pylori infection in patients with DGR [28]. Smoking has already been proposed as a risk factor for pyloric incompetence [16,22].…”
Section: Discussionmentioning
confidence: 99%
“…It implies that pyloric incompetence may be affected by the presence of an H. pylori infection. However, the relationship has still been controversial [27,28]. The causative mechanism of H. pylori infection for DGR remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, 7 , 8 the same lesions secondary to H. pylori infection or bile reflux have been reported as the most common endoscopic findings. 9 …”
Section: Dear Editormentioning
confidence: 99%